Assessment of social vulnerability to forest fire and hazardous facilities in Germany. (March 2023) - Fekete, Alexander; Nehren, Udo
Abstract: In recent years, Germany has seen an increase in forest fires, and many fires have occurred in military training areas that are difficult to access for firefighting. While casualties are still low and mostly restricted to firefighting personnel, settlements are also increasingly threatened. Increasing impacts from extreme events due to climate change will likely increase the ignition and spread of fires. More people are being affected by fires, and in need of external help to evacuate and cope with the resulting damages and losses. Forest fires also threaten military training site, with additional risks created by the presence of ammunition depots. Despite this hazard scenario, Germany so far lacks an overview of the spatial occurrence of forest fires and the related risk. This study develops a spatial exposure and social vulnerability assessment of settlements to forest fires in Germany. The results reveal that social vulnerability is an important variable in determining which settlements are potentially exposed to fire. Areas exposed to fire risk are characterised by having a higher proportion of women, a higher-than-average age, a higher number of young people under 18 years, a higher number of persons over 65 years and foreigners than the national average. Furthermore, exposed communities are characterised by higher rates of unoccupied housing units and lower living space per dwelling, as well as living in areas with high population densities within forested areas. The results can help to improve emergency management and spatial planning to prevent the development of fire risk areas.